iPod & iTunes for dummies - Bove, Tony (Wiley Pub., 2006)
The book includes chapters on: Firing up your Ipod; Setting up Itunes and your Ipod; Getting started; Playing Content; Searching and Browsing; Oranizing content with playlists; Baking your own discs; getting wired for playback; fine tuning the soud; etc. The language is simple and down to earth and includes Dummies famous simple diagrams and pointers.